2023
DOI: 10.3389/fendo.2023.1108616
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential biomarkers for non-obstructive azoospermia using WGCNA and machine learning algorithms

Qizhen Tang,
Quanxin Su,
Letian Wei
et al.

Abstract: ObjectiveThe cause and mechanism of non-obstructive azoospermia (NOA) is complicated; therefore, an effective therapy strategy is yet to be developed. This study aimed to analyse the pathogenesis of NOA at the molecular biological level and to identify the core regulatory genes, which could be utilised as potential biomarkers.MethodsThree NOA microarray datasets (GSE45885, GSE108886, and GSE145467) were collected from the GEO database and merged into training sets; a further dataset (GSE45887) was then defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Therefore, to answer the PICO questions formulated in the previous section, we organized and schematically summarized them in the upcoming tables. Indeed, the studies were divided based on the general topic they dealt with; therefore, the specific variables considered in each model included sperm retrieval (Table 2, four studies [37][38][39][40]); sperm quality, further divided into the investigation of sperm quality and morphology (Table 3a, seventeen studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]) and quality of sperm and environmental factors (Table 3b, four studies [58][59][60][61]); non-obstructive azoospermia (Table 4, three studies [62][63][64]); IVF outcome (Table 5, three studies [65][66][67]); environmental and medical factors (Table 6, twelve studies [68][69][70][71][72][73][74][75]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to answer the PICO questions formulated in the previous section, we organized and schematically summarized them in the upcoming tables. Indeed, the studies were divided based on the general topic they dealt with; therefore, the specific variables considered in each model included sperm retrieval (Table 2, four studies [37][38][39][40]); sperm quality, further divided into the investigation of sperm quality and morphology (Table 3a, seventeen studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]) and quality of sperm and environmental factors (Table 3b, four studies [58][59][60][61]); non-obstructive azoospermia (Table 4, three studies [62][63][64]); IVF outcome (Table 5, three studies [65][66][67]); environmental and medical factors (Table 6, twelve studies [68][69][70][71][72][73][74][75]…”
Section: Resultsmentioning
confidence: 99%
“…Certain studies have the limitation of being vaguely defined [54,58,59,66,70,71], thereby posing challenges in assessing the robustness of predictive models. It is crucial to clearly delineate the limitations of the study for appropriate interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…-Extracellular matrix protein 1 (ECM1): has been identified as a significant biomarker in the diagnosis of NOA. A study involving 119 seminal plasma samples from men with both normal spermatogenesis and azoospermia identified ECM1, along with TEX101, as key in differentiating between OA and NOA ( 74 ). They found that at a cutoff level of 2.3 μg/ml of ECM1 could distinguish OA from normal spermatogenesis with 100% specificity and OA from NOA with 73% specificity at 100% sensitivity.…”
Section: Potential Non-invasive Biomarkers In Noamentioning
confidence: 99%
“…In the context of identifying non-invasive biomarkers for sperm retrieval in cases of NOA, the integration of artificial intelligence (AI) with clinical and molecular data presents a transformative approach ( Figure 1 ). Some studies demonstrate the application of AI in this field, illustrating how machine learning and bioinformatics can significantly enhance the understanding and diagnosis of NOA ( 74 , 75 ). The integration of non-invasive biomarkers into the diagnostic and therapeutic algorithms for NOA patients holds the potential to revolutionize the clinical approach to male infertility, and to transform male infertility management into a realm of personalized medicine.…”
Section: Integrating Non-invasive Biomarkers Into Diagnostic and Ther...mentioning
confidence: 99%
See 1 more Smart Citation